Protecting the world's children : impact of the Convention on the Rights of the Child in diverse legal systems / UNICEF. (Cambridge University Press, 2007)
The book contains four studies that compare experiences from countries with similar legal traditions and examine how the Convention on the Rights of the Child has been integrated and harmonized with national legislation in specific countries. The book demonstrates how the CRC can be implemented in different country contexts in an effort to achieve children's rights uniformly across widely divergent legal traditions. It highlights key developments, identifies trends, and draws general conclusions that provide insight into the legal traditions at issue for advocacy in relationship to the implementation of the CRC, as well as to encourage practical actions. The book proposes a framework for enhancing compatibility of national legislation with human rights instruments and with the CRC in particular. The book endeavors to emphasize the CRC's ideology of indivisibility of rights, solidarity, and partnership in realizing children's rights. The book is a powerful advocacy tool for supporting the implementation of the CRC and Convention on the Elimination of all Forms of Discrimination Against Women (CEDAW).